Positive electrode active material and lithium secondary battery using the same
By controlling the volume structure and composition of lithium composite oxides, a cobalt-free lithium composite oxide is designed and a charged mixed layer is formed on the surface, which solves the problem of insufficient electrochemical performance and stability of the positive electrode active material with high cobalt content, and realizes a lithium-ion battery positive electrode material with high electrochemical performance and long life.
Patent Information
- Application Number
- JP2025022985
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-10-19
- Filing Date
- 2025-02-17
- Publication Date
- 2025-05-02
AI Technical Summary
After the existing lithium-ion battery positive electrode active materials have insufficient electrochemical performance and stability after reducing the cobalt content, resulting in a shortening of battery life, and the high cost of cobalt and unstable supply problems are difficult to solve.
By controlling the volume structure and composition of the lithium composite oxide, a cobalt-free lithium composite oxide is designed, with different nickel/manganese molar ratios on the outside and inside, and a charged hybrid layer is formed on the surface to improve crystal stability and electrochemical properties.
The high electrochemical performance and stability of cobalt-free lithium composite oxide is achieved, allowing it to replace traditional positive electrode active materials with high cobalt content, extend the service life of lithium-ion batteries, and reduce costs.
Smart Images

Figure 2025071126000001 
Figure 2025071126000002 
Figure 2025071126000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a cobalt-free positive electrode active material having improved thermal stability and electrochemical properties, and a lithium secondary battery using the same. [Background technology]
[0002] Batteries store electricity by using materials capable of electrochemical reaction at the positive and negative electrodes. A representative example of such batteries is a lithium secondary battery, which stores electrical energy by the difference in chemical potential when lithium ions are intercalated / deintercalated at the positive and negative electrodes.
[0003] The lithium secondary battery is manufactured by using a material capable of reversible intercalation / deintercalation of lithium ions as a positive electrode and a negative electrode active material, and filling an organic electrolyte or a polymer electrolyte between the positive electrode and the negative electrode.
[0004] A typical material used as a positive electrode active material for lithium secondary batteries is a lithium composite oxide. The lithium composite oxide is LiCoO 2 , LiMn 2 O 4 , LiNiO 2 , LiMnO 2 Alternatively, as disclosed in Korean Patent Publication No. 10-2015-0069334 (published on June 23, 2015), there are oxides in which Ni, Co, Mn, Al, etc. are combined.
[0005] Commercially available lithium composite oxides such as nickel-cobalt-manganese (NCM) contain cobalt as an essential element to achieve a trade-off between electrochemical properties and stability.
[0006] However, recently, with the rapid growth of the lithium secondary battery market, the cost of raw materials has increased, and so the market is faced with another problem of cost reduction. In particular, the positive electrode active material accounts for the largest proportion of the cost in lithium secondary batteries, and among them, cobalt, an essential element in lithium composite oxides such as nickel-cobalt-manganese (NCM), is not only the most expensive metal but also has a relatively large supply and demand instability, so there is an increasing demand for cost-reduced positive electrode active materials by adopting cobalt-free compositions.
[0007] Meanwhile, even if the cobalt content is reduced slightly from a commercially available lithium composite oxide such as nickel-cobalt-manganese (NCM), the resistance of the positive electrode active material increases, and therefore a decrease in electrochemical properties such as the rate characteristics of a lithium secondary battery using the positive electrode active material is unavoidable. In addition, as the cobalt content of the lithium composite oxide decreases, the stability of the particles decreases rapidly, and the life of a lithium secondary battery using the lithium composite oxide as a positive electrode active material may be prematurely deteriorated. Summary of the Invention [Problem to be solved by the invention]
[0008] In the lithium secondary battery market, the growth of lithium secondary batteries for electric vehicles is playing a leading role in driving the market, and as a result, the demand for positive electrode active materials used in lithium secondary batteries is also continuously increasing.
[0009] For example, lithium secondary batteries using lithium iron phosphate (LFP) have traditionally been used primarily from the standpoint of ensuring safety, but recently there has been a trend toward expanding use of nickel-based lithium composite oxides, which have a larger energy capacity per weight than LFP.
[0010] In addition, nickel-based lithium composite oxides, which are currently mainly used as positive electrode active materials for high-capacity lithium secondary batteries, essentially contain ternary metal elements such as nickel, cobalt, and manganese or nickel, cobalt, and aluminum. However, since the supply and demand of cobalt is unstable and it is particularly expensive compared to other raw materials, a new positive electrode active material with a reduced cobalt content or an absence of cobalt is required.
[0011] Considering these circumstances, cobalt-free lithium composite oxides, which do not contain cobalt, are attracting attention from commercially available ternary lithium composite oxides having a nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) composition.
[0012] The cobalt-free lithium composite oxide meets the above-mentioned market expectations, but has limitations in that its electrochemical properties and stability are insufficient to replace commercially available positive electrode active materials such as nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) ternary lithium composite oxides.
[0013] For example, as described above, as the cobalt content decreases in commercially available ternary lithium composite oxides having a nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) composition, the resistance of the positive electrode active material increases, and therefore, a lithium secondary battery using the positive electrode active material inevitably suffers from a decrease in electrochemical characteristics such as rate characteristics.
[0014] In addition, as the cobalt content in the lithium composite oxide decreases, the particle stability (crystal stability, thermal stability, particle strength, etc.) decreases rapidly, which may cause a problem that the life of a lithium secondary battery using the lithium composite oxide as a positive electrode active material may be prematurely deteriorated.
[0015] However, it is true that the electrochemical properties and stability of conventional cobalt-free lithium composite oxides are somewhat lower than those of commercially available ternary lithium composite oxides having nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) compositions. However, the present inventors have confirmed that the cobalt-free lithium composite oxide can exhibit electrochemical properties and stability at a commercially viable level by newly designing the bulk structure and bulk composition of the cobalt-free lithium composite oxide.
[0016] Accordingly, an object of the present invention is to provide a cobalt-free positive electrode active material having improved thermal stability and electrochemical properties through control of the bulk structure and bulk composition, and a lithium secondary battery using the same. [Means for solving the problem]
[0017] According to one aspect of the present invention for solving the above-mentioned technical problems, there is provided a positive electrode active material including a lithium composite oxide containing at least nickel and manganese, wherein the lithium composite oxide is partitioned into an outer bulk surrounding a surface of an inner bulk.
[0018] In one embodiment, the Ni / Mn molar ratio of the outer bulk is preferably smaller than the Ni / Mn molar ratio of the inner bulk. Specifically, the Ni / Mn molar ratio of the inner bulk may be greater than 4.26 and less than 9.00, and the Ni / Mn molar ratio of the outer bulk may be greater than 1.0 and less than 2.33.
[0019] In one embodiment, the volume fraction of the external bulk in the total volume of the lithium composite oxide is preferably smaller than the volume fraction of the internal bulk. More specifically, the volume fraction of the external bulk in the total volume of the lithium composite oxide may be 7.4% or more and less than 27.1%.
[0020] As described above, the cobalt-free lithium composite oxide can exhibit electrochemical properties and stability at a commercially viable level by controlling the bulk structure and bulk composition of the lithium composite oxide.
[0021] In one embodiment, a cation mixed layer may be present on at least a portion of the surface of the outer bulk by controlling the bulk structure and bulk composition of the lithium composite oxide. In this case, the cation mixed ratio of the outer bulk is designed to be greater than the cation mixed ratio of the inner bulk, thereby increasing the crystal stability of the surface of the lithium composite oxide and simultaneously reducing the cation mixed ratio in the inner bulk to prevent deterioration of the overall electrochemical properties of the lithium composite oxide.
[0022] In one embodiment, the lithium composite oxide may be represented by the following Chemical Formula 1:
[0023] [C1] Li a Ni 1-(b+c+d) Mn b M1 c M2 d O 2-e X e
[0024] (where: M1 and M2 are each independently at least one selected from Ti, Zr, Nb, Al, B, V, W, Ca, K, S, P, Sr, Ba, Mn, Ce, Hf, Ta, Cr, Mg, Fe, Zn, Si, Y, Ga, Sn, Mo, Ge, Nd, Gd, and Cu; M1 and M2 do not overlap with each other, X is a halogen element present in a state of substituting oxygen present in the lithium composite oxide, 0.95≦a≦1.05, 0 <b≦0.5、0≦c≦0.05、0≦d≦0.05、0≦e≦0.10である)
[0025] In another embodiment, a coating layer including a metal oxide represented by the following Chemical Formula 2 may be formed on at least a portion of the surface of the lithium composite oxide.
[0026] [Case 2] Li f M3 g O h
[0027] (where: M3 is at least one selected from Ni, Mn, Co, Ti, Zr, Nb, Al, B, V, W, Ca, K, S, P, Sr, Ba, Mn, Ce, Hf, Ta, Cr, Mg, Fe, Zn, Si, Y, Ga, Sn, Mo, Ge, Nd, Gd, and Cu; 0≦f≦10, 0≦g≦8, 2≦h≦13, except when f and g are both 0.
[0028] The coating layer formed on at least a portion of the surface of the lithium composite oxide may contribute to improving the electrical conductivity of the outer bulk, which is lower than that of the inner bulk.
[0029] According to another aspect of the present invention, there is provided a positive electrode including the above-described positive electrode active material.
[0030] According to yet another aspect of the present invention, there is provided a lithium secondary battery using the above-mentioned positive electrode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] In order to make the present invention easier to understand, certain terms are defined herein for convenience.Unless otherwise defined herein, scientific and technical terms used in the present invention shall have the meanings that are commonly understood by those of ordinary skill in the art.In addition, unless otherwise specified by the context, singular terms shall be understood to include their plural forms, and plural terms shall be understood to include their singular forms.
[0032] positive electrode active material According to one aspect of the present invention, there is provided a positive electrode active material including a lithium composite oxide containing at least nickel and manganese.
[0033] The lithium composite oxide contains lithium other than nickel and manganese, and is a composite metal oxide having a layered crystal structure capable of intercalating / deintercalating lithium ions.
[0034] The lithium composite oxide defined in the present application is a composite metal oxide that is distinguished from overlithiated layered oxide (OLO) in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group exist in a solid solution state, since the ratio of manganese among all metal elements is relatively high (e.g., 50 mol % or more) compared to commercially available ternary lithium composite oxides.
[0035] The lithium composite oxide defined herein may be a particle comprising at least one primary particle.
[0036] When the lithium composite oxide exists as a single primary particle, the lithium composite oxide may be referred to as a single particle, whereas when the lithium composite oxide exists as an aggregate of a plurality of primary particles, the lithium composite oxide may be referred to as a secondary particle.
[0037] The positive electrode active material may contain at least one selected from a lithium composite oxide that exists as a single particle and a lithium composite oxide that exists as secondary particles formed by aggregation of a plurality of primary particles.
[0038] The primary particles constituting the lithium composite oxide may have a rod shape, an elliptical shape, and / or an irregular shape. Furthermore, unless otherwise intended in the manufacturing process, primary particles of various shapes are present in the same positive electrode active material.
[0039] The primary particles constituting the lithium composite oxide defined in the present application may have an average particle size of 0.1 μm to 5 μm, preferably 0.1 μm to 1.0 μm, and more preferably 0.25 μm to 0.75 μm. The average particle size of the primary particles can be calculated as the average value of the major axis length and the minor axis length of the primary particles.
[0040] When the average particle size of the primary particles is less than 0.1 μm, the specific surface area of the lithium composite oxide (secondary particles) composed of the primary particles is relatively large, which may increase the possibility of a side reaction occurring between the lithium composite oxide and an electrolyte during storage or operation of the lithium secondary battery.
[0041] On the other hand, when the average particle size of the primary particles is larger than 5 μm, the growth of the primary particles is excessively induced, and the diffusion path of the lithium ions in the primary particles is also lengthened. When the diffusion path of the lithium ions in the primary particles is too long, the mobility of the lithium ions in the primary particles and the diffusibility of the lithium ions through the primary particles are reduced, which causes an increase in the resistance of the lithium composite oxide (secondary particles) composed of the primary particles.
[0042] In order to reduce the specific surface area of the lithium composite oxide and at the same time prevent a decrease in the mobility of lithium ions within the primary particles and the diffusibility of lithium ions between adjacent primary particles, the average particle size of the primary particles is preferably 0.1 μm to 5 μm, more preferably 0.1 μm to 1.0 μm, and even more preferably 0.25 μm to 0.75 μm.
[0043] When the lithium composite oxide exists as secondary particles formed by agglomeration of a plurality of primary particles, the secondary particles may have an average particle size of 1 μm to 30 μm. The average particle size of the secondary particles may vary depending on the number of the primary particles constituting the secondary particles.
[0044] In the lithium composite oxide, the nickel content (mol%) calculated based on all elements excluding lithium may be 50 mol% or more and less than 95 mol%, preferably 60 mol% or more and 90 mol% or less, and more preferably 75 mol% or more and 85 mol% or less.
[0045] When the content of nickel in the lithium composite oxide is less than 50 mol%, the proportion of lithium composite oxide having a spinel crystal structure in the positive electrode active material may be increased. As the proportion of lithium composite oxide having a spinel crystal structure in the positive electrode active material increases, a higher operating voltage is required, and the capacity characteristics of a lithium secondary battery using the lithium composite oxide as a positive electrode active material may be reduced. In addition, as the content of manganese in the lithium composite oxide increases, the overall cation mixing in the lithium composite oxide may increase.
[0046] Specifically, the charge of the entire transition metal constituting the lithium composite oxide is preferably in a trivalent state in order to exhibit a stable charge neutrality state. In this case, when synthesizing a lithium composite oxide having a low cobalt content and a high manganese content, Mn 4+ is in excess, so to indicate a charge neutral state, Ni 3+ Instead of Ni 2+ The content of Ni increases. 2+ (0.69Å) is Li + (0.76 Å), they can occupy the 3a site of Li in the crystal structure of the lithium composite oxide, and this occupancy phenomenon is called cation mixing.
[0047] On the other hand, when nickel is present in excess in the lithium composite oxide, the lithium composite oxide is LiNiO 2 It shows the following characteristics: 2has low thermal stability and, if an internal short circuit occurs due to external pressure or the like while the battery is being charged, the positive electrode active material may decompose on its own or a side reaction may occur at the interface or surface between the electrolyte and the positive electrode active material, resulting in the lithium secondary battery exploding or catching fire.
[0048] Meanwhile, in the lithium composite oxide, the manganese content (mol%) calculated based on all elements excluding lithium may be more than 5 mol% and not more than 50 mol%, preferably 10 mol% or more and 40 mol% or less, and more preferably 10 mol% or more and 30 mol% or less.
[0049] In order to design the bulk composition of the lithium composite oxide to be cobalt-free, the manganese content in the lithium composite oxide is preferably at least 5 mol % or more.
[0050] On the other hand, when the manganese content in the lithium composite oxide is more than 50 mol%, the proportion of the lithium composite oxide having a spinel crystal structure in the positive electrode active material may be increased. As described above, the higher the proportion of the lithium composite oxide having a spinel crystal structure in the positive electrode active material, the higher the operating voltage required, and the lower the capacity characteristics of the lithium secondary battery using the lithium composite oxide as the positive electrode active material. In addition, as the manganese content in the lithium composite oxide increases, the overall cation mixing in the lithium composite oxide may increase.
[0051] The lithium composite oxide defined herein is partitioned into an outer bulk surrounding the surface of an inner bulk.
[0052] In this case, the inner bulk and the outer bulk can be distinguished by the Ni / Mn molar ratio. For example, when synthesizing the hydroxide precursor of the lithium composite oxide using a coprecipitation method while continuously changing the concentrations of nickel and manganese present in the metal salt aqueous solution, a hydroxide precursor in which the concentrations of nickel and manganese continuously change from the center to the surface can be obtained.
[0053] However, as described above, when the nickel and manganese concentrations change continuously from the center to the surface of the hydroxide precursor, the Ni / Mn molar ratio also changes continuously from the center to the surface of the hydroxide precursor, so that it is not possible to distinguish between the inner bulk and the outer bulk based on the Ni / Mn molar ratio.
[0054] Meanwhile, for example, when an inner bulk is synthesized using a first metal salt aqueous solution in which the molar ratio of nickel and manganese is designed to be 85:15, and then an outer bulk is synthesized using a second metal salt aqueous solution in which the molar ratio of nickel and manganese is designed to be 50:50, the Ni / Mn molar ratio of the inner bulk and the Ni / Mn molar ratio of the outer bulk depend on the Ni / Mn molar ratio of the first metal salt aqueous solution and the Ni / Mn molar ratio of the second metal salt aqueous solution, and thus the inner bulk and the outer bulk can be distinguished based on the Ni / Mn molar ratio.
[0055] The concentration of the transition metal in the lithium composite oxide can be measured by various known methods, for example, by performing line scanning on the concentration change of the target transition metal after EDS mapping of the cross section of the lithium composite oxide.
[0056] In addition, the acceleration voltage V acc There is an Energy Profiling-Energy Dispersive X-ray Spectroscopy (EP-EDS) method that measures the concentration of a target transition metal at the depth where the electron beam penetrates depending on the strength of the electron beam.
[0057] In one embodiment, the Ni / Mn molar ratio of the external bulk is preferably smaller than the Ni / Mn molar ratio of the internal bulk. When the Ni / Mn molar ratio of the external bulk is designed to be smaller than the Ni / Mn molar ratio of the internal bulk, the Mn content in the external bulk is higher than the Mn content in the internal bulk.
[0058] By decreasing the Mn content and increasing the Ni content in the inner bulk, the cation mixing in the inner bulk is decreased, and thus, improvement in capacity and rate characteristics can be expected from the inner bulk.
[0059] In addition, by increasing the Mn content in the external bulk, the mixed cations present in the lithium composite oxide can be made to be present locally in the external bulk and further on the surface of the lithium composite oxide.
[0060] That is, as long as the cation mixing ratio and the manganese content are proportional to each other in the lithium composite oxide defined herein, the cation mixing ratio of the outer bulk may be greater than the cation mixing ratio of the inner bulk.
[0061] When the mixed cations are present locally on the surface of the lithium composite oxide, a mixed cation layer may be present on at least a portion of the surface of the lithium composite oxide.
[0062] Unlike the mixed cations present in the internal bulk, the mixed cations present in the external bulk can improve the surface stability of the lithium composite oxide and contribute to improving the stability (crystal stability, thermal stability, particle strength, etc.) of the lithium composite oxide.
[0063] The cation mixed layer may have at least one phase selected from a layered structure, a rock salt structure, and a spinel structure. In this case, the layered structure present in the cation mixed layer may be different from the layered structures present in at least the inner bulk and the outer bulk.
[0064] Specifically, in order to reduce cation mixing in the inner bulk and induce improved capacity and rate characteristics from the inner bulk, the molar ratio of Ni to all metal elements excluding lithium in the inner bulk is 0.7 or more and less than 1.0, and the Ni / Mn molar ratio of the inner bulk may be designed to be greater than 4.26 and less than 9.00, preferably greater than 4.56 and less than 7.33.
[0065] If the Ni / Mn molar ratio of the inner bulk is 4.26 or less, the Mn content in the inner bulk becomes too high, and the cation mixing in the inner bulk may increase, whereas if the Ni / Mn molar ratio of the inner bulk is 9.00 or more, the Ni content in the inner bulk becomes too high, and the thermal stability of the inner bulk may decrease.
[0066] In addition, in order to concentrate the mixed cations present in the lithium composite oxide on the surface of the lithium composite oxide to improve the surface stability and overall electrochemical properties of the lithium composite oxide, the molar ratio of Ni to all metal elements excluding lithium in the external bulk may be designed to be 0.5 to less than 0.8, and the Ni / Mn molar ratio of the external bulk may be designed to be 1.0 to less than 2.33, preferably 1.0 to 1.5.
[0067] When the Ni / Mn molar ratio of the external bulk is less than 1.0, the Mn content in the external bulk becomes excessively high, and an unintended phase transition may occur in the external bulk. On the other hand, when the Ni / Mn molar ratio of the external bulk is 2.33 or more, the cation mixture present in the lithium composite oxide may be uniformly dispersed in the internal bulk and the external bulk instead of being present locally in the external bulk.
[0068] In addition, as described above, in order to allow a mixture of cations present in the lithium composite oxide to be locally present in the external bulk, the ratio of the Ni content (mol%) of the external bulk to the Ni content (mol%) of the internal bulk may be designed to be more than 0.556 and less than 0.740, preferably 0.588 to 0.732, and the ratio of the Mn content (mol%) of the external bulk to the Mn content (mol%) of the internal bulk may be designed to be 2.2 to less than 5.0, preferably 2.2 to 3.75.
[0069] Meanwhile, in order for the cobalt-free lithium composite oxide to exhibit electrochemical properties and stability at a level that allows commercialization, the Ni / Mn molar ratio of the inner bulk and the outer bulk must be designed within the range defined above, and the volume fraction of the inner bulk and the outer bulk must also be controlled.
[0070] In one embodiment, the volume fraction of the outer bulk in the total volume of the lithium composite oxide is preferably smaller than the volume fraction of the inner bulk.
[0071] By designing the volume fraction of the external bulk to be smaller than the volume fraction of the internal bulk, the ratio of the region where the cation mixture is present in the total volume of the lithium composite oxide is reduced, so that the external bulk where the cation mixture is present can be locally present on the surface of the lithium composite oxide, thereby simultaneously improving the surface stability and electrochemical properties of the lithium composite oxide.
[0072] Specifically, the volume fraction of the external bulk in the total volume of the lithium composite oxide can be designed to be 7.4% or more and less than 27.1%, preferably 8.7% or more and 24.7% or less.
[0073] When the volume fraction of the external bulk is less than 7.4%, the volume occupied by the external bulk in the total volume of the lithium composite oxide is small, so that the mixed cations present in the lithium composite oxide may not be effectively concentrated in the external bulk.On the other hand, when the volume fraction of the external bulk is 27.1% or more, the volume occupied by the external bulk where the mixed cations in the lithium composite oxide are present becomes too large, so that the electrochemical properties, including the capacity characteristics and rate characteristics, of the lithium composite oxide may be deteriorated.
[0074] The volume fraction of the internal bulk in the total volume of the lithium composite oxide may be calculated using a ratio of the radius of the internal bulk to the radius of the lithium composite oxide. Specifically, the volume fraction of the internal bulk in the total volume of the lithium composite oxide may be expressed as a ratio of the volume calculated using the radius of the internal bulk to the total volume of the lithium composite oxide calculated using the radius of the lithium composite oxide ([volume of the internal bulk / total volume of the lithium composite oxide]*100).
[0075] In addition, the volume fraction of the external bulk in the total volume of the lithium composite oxide may be calculated using the ratio of the thickness of the external bulk to the radius of the lithium composite oxide. Specifically, the volume fraction of the external bulk in the total volume of the lithium composite oxide may be expressed as a ratio of the difference between the total volume of the lithium composite oxide calculated using the radius of the lithium composite oxide and the volume calculated using the radius of the internal bulk ([total volume of the lithium composite oxide-volume of the internal bulk / total volume of the lithium composite oxide]*100).
[0076] In order for the volume fraction of the outer bulk to the total volume of the lithium composite oxide to satisfy the above definition, the ratio of the thickness of the outer bulk to the radius of the lithium composite oxide may be designed to be greater than 0.025 and less than 0.10, preferably 0.030 or more and 0.090 or less.
[0077] When the ratio of the thickness of the external bulk to the radius of the lithium composite oxide is 0.025 or less, the volume of the external bulk in the total volume of the lithium composite oxide may be excessively small.On the other hand, when the ratio of the thickness of the external bulk to the radius of the lithium composite oxide is 0.10 or more, the volume of the external bulk in which mixed cations exist in the lithium composite oxide may be excessively large, and the electrochemical properties, including the capacity characteristics and rate characteristics, of the lithium composite oxide may be deteriorated.
[0078] In one embodiment, the lithium composite oxide may be a cobalt-free lithium composite oxide represented by the following Chemical Formula 1. The composition represented by the following Chemical Formula 1 represents an average composition of the inner bulk and the outer bulk.
[0079] [C1] Li a Ni 1-(b+c+d) Mn b M1 c M2 d O 2-e X e
[0080] (where: M1 and M2 are each independently at least one selected from Ti, Zr, Nb, Al, B, V, W, Ca, K, S, P, Sr, Ba, Mn, Ce, Hf, Ta, Cr, Mg, Fe, Zn, Si, Y, Ga, Sn, Mo, Ge, Nd, Gd, and Cu; M1 and M2 do not overlap with each other, X is a halogen element present in a state of substituting oxygen present in the lithium composite oxide, 0.95≦a≦1.05, 0 <b≦0.5、0≦c≦0.05、0≦d≦0.05、0≦e≦0.10である)
[0081] In the chemical formula 1, “1−(b+c+d)”, which indicates the content (molar ratio) of nickel in the lithium composite oxide, may be 0.5 or more and less than 0.95, preferably 0.6 or more and 0.9 or less, and more preferably 0.75 or more and 0.85 or less.
[0082] In addition, in the chemical formula 1, "b" indicating the content (molar ratio) of manganese in the lithium composite oxide may be more than 0 and not more than 0.50, preferably more than 0.05 and not more than 0.5, more preferably 0.10 or more and 0.40 or less, and more preferably 0.10 or more and 0.30 or less.
[0083] Meanwhile, by making the Ni / Mn molar ratio of the external bulk smaller than that of the internal bulk, electrochemical properties including capacity and rate characteristics expected from the internal bulk can be improved, and by concentrating mixed cations in the external bulk, the surface stability of the lithium composite oxide can be improved. However, when mixed cations are concentrated in the external bulk, the electrical conductivity of the surface of the lithium composite oxide decreases, and thus the charge-transfer and / or diffusivity (i.e., surface kinetic) of lithium ions on the surface of the lithium composite oxide can decrease.
[0084] Accordingly, when a coating layer including a metal oxide represented by the following Formula 2 is formed on at least a portion of the surface of the lithium composite oxide (i.e., at least a portion of the surface of the outer bulk), the electrical conductivity of the outer bulk, which is relatively lower than that of the inner bulk, can be improved, and the surface kinetics of the lithium composite oxide can be improved.
[0085] [Case 2] Li f M3 g O h
[0086] (where: M3 is at least one selected from Ni, Mn, Co, Ti, Zr, Nb, Al, B, V, W, Ca, K, S, P, Sr, Ba, Mn, Ce, Hf, Ta, Cr, Mg, Fe, Zn, Si, Y, Ga, Sn, Mo, Ge, Nd, Gd, and Cu; 0≦f≦10, 0≦g≦8, 2≦h≦13, except when f and g are both 0.
[0087] Non-limiting examples of the metal oxide represented by Formula 2 include Li g Zr h O i , Li g Ti h O i , Li g Ni h O i , Li g Nb h O i , Li g Co h O i , Li g S h O i , Li g Al h O i , Co h O i , Mn h O i , Al h O i , Si h O i , Zr h O i , Ti h O i In addition, a different metal oxide represented by the above Chemical Formula 2 may be independently present on at least a part of the surface of the lithium composite oxide.
[0088] A surface where adjacent primary particles in the secondary particle are in contact with each other may be referred to as an interface between the primary particles, and the interface between the primary particles may be defined as a grain boundary between the primary particles. Also, the primary particles may be separated from the adjacent primary particles to form voids within the secondary particles.
[0089] The surface of the secondary particle formed by agglomeration of a plurality of primary particles corresponds to the exposed surface of the primary particles present on the surface portion of the secondary particle.
[0090] The coating layer is defined as a region where the metal oxide is present on the surface of the primary particles and / or the secondary particles, and the coating layer may be formed entirely or partially on the surface of the primary particles and / or the secondary particles. When the coating layer is partially formed on the surface of the primary particles and / or the secondary particles, the shape of the coating layer may be referred to as an island shape.
[0091] The metal oxide may be present in a state where it is physically and / or chemically bound to the surface of the primary particles and / or the secondary particles, or may be present in a state where it is partially solid-dissolved.
[0092] The coating layer present inside the secondary particles may be formed by diffusing the metal oxide from the surface of the secondary particles toward the center of the secondary particles along the crystal grain boundaries between the primary particles. As the metal oxide diffuses from the surface of the secondary particles toward the center of the secondary particles, at least one of the elements (e.g., M3) contained in the metal oxide may exhibit a concentration gradient that decreases from the surface of the secondary particles toward the center of the secondary particles.
[0093] The gradient of the metal oxide can be measured by a method of line scanning the concentration change of the element specific to the metal oxide after EDS mapping after cross-section processing of the lithium composite oxide, or by an Energy Profiling-Energy Dispersive X-ray Spectroscopy (EP-EDS) method of measuring the concentration of the element specific to the metal oxide according to the penetration depth of an electron beam irradiated to the surface of the lithium composite oxide.
[0094] Lithium secondary battery According to yet another aspect of the present invention, a positive electrode may be provided, the positive electrode active material layer including a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector. Here, the positive electrode active material layer may include a positive electrode active material according to various embodiments of the present invention. Therefore, since the positive electrode active material is as described above, detailed description will be omitted for convenience, and only the remaining components not described above will be described below.
[0095] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may usually have a thickness of 3 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0096] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition containing the positive electrode active material, a conductive material, and optionally a binder, on the positive electrode current collector.
[0097] At this time, the positive electrode active material may be included in an amount of 80 to 99 wt%, more specifically, 85 to 98.5 wt%, based on the total weight of the positive electrode active material layer. When included in this content range, excellent capacity characteristics can be exhibited, but the amount is not necessarily limited thereto.
[0098] The conductive material is used to impart electrical conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed. Specific examples include graphite such as natural graphite and artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon-based materials such as carbon fibers, metal powders or metal fibers such as copper, nickel, aluminum, and silver, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, and conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in combination. The conductive material may be contained in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode active material layer.
[0099] The binder serves to improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and among these, one type alone or a mixture of two or more types may be used. The binder may be included in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode active material layer.
[0100] The positive electrode may be manufactured by a typical method for manufacturing a positive electrode, except for using the positive electrode active material. Specifically, the positive electrode may be manufactured by dissolving or dispersing the positive electrode active material and, optionally, a binder and a conductive material in a solvent to prepare a positive electrode slurry composition, which is then coated on a positive electrode current collector, followed by drying and rolling.
[0101] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to provide a viscosity that allows excellent thickness uniformity when applied to manufacture a positive electrode, taking into consideration the coating thickness of the slurry and the production yield.
[0102] In another embodiment, the positive electrode may be manufactured by casting the positive electrode slurry composition on a separate support, peeling the positive electrode slurry composition from the support, and laminating the resulting film on a positive electrode current collector.
[0103] According to yet another aspect of the present invention, there may be provided an electrochemical device including the above-mentioned positive electrode. The electrochemical device may be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.
[0104] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode facing the positive electrode, and a separator and an electrolyte interposed between the positive electrode and the negative electrode. Here, since the positive electrode is as described above, a detailed description thereof will be omitted for convenience, and only the remaining components not described above will be described in detail below.
[0105] The lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.
[0106] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0107] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may generally have a thickness of 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.
[0108] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition containing the negative electrode active material, a conductive material, and optionally a binder, on the negative electrode current collector.
[0109] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon, metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys, and SiO β (0<β<2), SnO 2, a metal oxide capable of doping and dedoping lithium, such as vanadium oxide or lithium vanadium oxide, or a composite containing the metallic compound and a carbonaceous material, such as a Si-C composite or a Sn-C composite, may be used. Any one or a mixture of two or more of these may be used. A thin film of metallic lithium may be used as the negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon may be used as the carbon material. Representative examples of low-crystalline carbon include soft carbon and hard carbon, and representative examples of high-crystalline carbon include amorphous, plate-like, scaly, spherical or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.
[0110] The negative electrode active material may be included in an amount of 80 to 99 wt % based on the total weight of the negative electrode active material layer.
[0111] The binder is a component that aids in bonding between the conductive material, the active material, and the current collector, and may be added in an amount of usually 0.1 to 10 wt% based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.
[0112] The conductive material may be added as a component for further improving the conductivity of the negative electrode active material in an amount of 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery, and may be, for example, graphite such as natural graphite or artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black, conductive fibers such as carbon fibers or metal fibers, metal powders such as carbon fluoride, aluminum, or nickel powder, conductive whiskey such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, or conductive materials such as polyphenylene derivatives.
[0113] In one embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating. Alternatively, the negative electrode slurry composition may be cast on a separate support, and then peeled off from the support to obtain a film, which may be laminated on the negative electrode current collector.
[0114] In another embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating, or by casting the negative electrode slurry composition on a separate support and peeling the composition from the support to obtain a film, which may be laminated on the negative electrode current collector.
[0115] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode to provide a passage for lithium ions to move. Any separator generally used in lithium secondary batteries may be used without any particular limitation. In particular, it is preferable that the separator has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high-melting point glass fiber, a polyethylene terephthalate fiber, or the like, may be used. In addition, in order to ensure heat resistance or mechanical strength, a separator coated with a ceramic component or a polymer material may be used, and may be selectively used as a single-layer or multi-layer structure.
[0116] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.
[0117] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0118] The organic solvent may be used without any particular limitation as long as it serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone, an ether solvent such as dibutyl ether or tetrahydrofuran, a ketone solvent such as cyclohexanone, an aromatic hydrocarbon solvent such as benzene or fluorobenzene, dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that may be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the performance of the electrolyte may be excellent if the cyclic carbonate and the chain carbonate are mixed at a volume ratio of about 1:1 to about 1:9.
[0119] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. 6 , LiClO 4 , LiAsF 6 , LiBF 4 , LiSbF 6 , LiAlO 4 , LiAlCl 4 , LiCF 3 SO 3 , LiC 4 F 9 SO 3 , LiN(C 2 F 5 SO 3 ), LiN(C 2 F 5 SO 2 ) 2 , LiN(CF 3 SO 2 ) 2 , LiCl, LiI, or LiB(C 2 O 4 ) 2 The lithium salt may be used at a concentration within the range of 0.1 to 2.0 M. When the lithium salt concentration is within this range, the electrolyte has appropriate conductivity and viscosity, and therefore can exhibit excellent electrolyte performance and can effectively migrate lithium ions.
[0120] When the electrolyte used in the present application is a solid electrolyte, for example, a solid inorganic electrolyte such as a sulfide-based solid electrolyte, an oxide-based solid electrolyte, a nitride-based solid electrolyte, or a halide-based solid electrolyte may be used, and preferably, a sulfide-based solid electrolyte may be used.
[0121] As the material of the sulfide-based solid electrolyte, a solid electrolyte containing Li, an X element (wherein X is at least one selected from P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In) and S may be used. Examples of the sulfide-based solid electrolyte material include Li 2 SP2 S 5 , Li 2 SP 2 S-LiX (where X is a halogen element such as I or Cl), Li 2 SP 2 S 5 -Li 2 O, Li 2 SP 2 S 5 -Li 2 O-LiI, Li 2 S-SiS 2 , Li 2 S-SiS 2 - LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 - LiI, Li 2 S-SiS 2 -P 2 S5-LiI, Li 2 S.B. 2 S 3 , Li 2 SP 2 S 5 -ZmSn (where m and n are integers and Z is Ge, Zn or Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li p MO q (where p, q are integers and M is P, Si, Ge, B, Al, Ga or In).
[0122] The solid electrolyte, preferably the sulfide-based solid electrolyte, may be amorphous or crystalline, or may be in a mixed amorphous and crystalline state.
[0123] As a material for oxide-based solid electrolytes, Li7 La 3 Zr 2 O 12 , Li 7-x La 3 Zr 1-x Nb x O 12 , Li 7-3x La 3 Zr 2 Al x O 12 , Li 3x La 2 / 3-x TiO 3 , Li 1+x Al x Ti 2-x (PO 4 ) 3 , Li 1+x Al x Ge 2-x (PO 4 ) 3 , Li 3 PO 4 , Li 3+x PO 4-x N x (LiPON), Li 2+2x Zinc 1-x GeO 4 (LISICON), etc.
[0124] The solid electrolyte may be disposed as a separate layer (solid electrolyte layer) between the positive electrode and the negative electrode. The solid electrolyte may be included in a portion of the positive electrode active material layer of the positive electrode, independent of the solid electrolyte layer, or the solid electrolyte may be included in a portion of the negative electrode active material layer of the negative electrode, independent of the solid electrolyte layer.
[0125] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5% by weight based on the total weight of the electrolyte.
[0126] As described above, the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and life characteristics, and is therefore useful in the fields of portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).
[0127] The external shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, etc. Furthermore, the lithium secondary battery can be used not only as a battery cell used as a power source for a small device, but also preferably as a unit battery for a medium- to large-sized battery module including a plurality of battery cells.
[0128] According to yet another aspect of the present invention, there may be provided a battery module including the lithium secondary battery as a unit cell and / or a battery pack including the same.
[0129] The battery module or the battery pack can be used as a power source for one or more medium- to large-sized devices, such as a power tool, an electric vehicle (Electric Vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV), or a power storage system.
[0130] The present invention will be described in more detail below with reference to examples. However, these examples are for the purpose of illustrating the present invention, and the scope of the present invention is not to be construed as being limited by these examples.
[0131] Production Example 1. Production of positive electrode active material Example 1 (a) A hydroxide precursor separated into an inner bulk and an outer bulk surrounding the surface of the inner bulk was synthesized by a co-precipitation method.
[0132] First, the first metal salt aqueous solution was prepared by mixing nickel sulfate and manganese sulfate weighed so that the molar ratio of Ni:Mn was 83:17, and then the solution was stirred at 450 rpm and reacted for 1,437 minutes to obtain Ni. 0.83 Mn 0.17 (OH) 2 The inner bulk had an average composition of 4.850 μm and a radius of 4.850 μm. The volume of the inner bulk calculated using the radius of the inner bulk was 477.6 μm. 3 It was.
[0133] (b) After the synthesis of the inner bulk was completed, an aqueous solution of a second metal salt was added to the reactor, which was prepared by mixing nickel sulfate and manganese sulfate weighed to have a molar ratio of Ni:Mn of 50:50, and reacted for 153 minutes while stirring at 450 rpm to form Ni on the surface of the inner bulk. 0.50 Mn 0.50 (OH) 2The volume of the outer bulk calculated using the thickness of the outer bulk was 45.7 μm. 3 It was.
[0134] In this case, the average composition of the hydroxide precursor including the inner bulk and the outer bulk finally synthesized is Ni 0.80 Mn 0.20 (OH) 2 and the radius was 5.0 μm.
[0135] (c) The hydroxide precursor obtained in step (b) is mixed with LiOH (weighed out so that Li has a molar ratio of 1.02 with respect to the total metal element content based on the final product), and then calcined in a calcination furnace. 2 While maintaining the atmosphere, the temperature was increased to 820° C. at 2° C. per minute, and heat treatment was performed at 820° C. for 8 hours to obtain a lithium composite oxide having a radius of 5.0 μm.
[0136] Example 2 ~ Example 8 The positive electrode active materials according to Examples 2 to 8 were prepared in the same manner as in Example 1, except for the conditions described in Tables 1 and 2 below.
[0137] [Table 1]
[0138] [Table 2]
[0139] Example 9 The lithium composite oxide obtained in step (c) of Example 1, TiO 2 and ZrO 2 After mixing, it is baked in a furnace. 2 While maintaining the atmosphere, the temperature was raised to 720°C at a rate of 2°C per minute, and the material was heat-treated at 720°C for 8 hours. 2 and ZrO 2were weighed out so that the contents of Ti and Zr were each 0.1 mol % based on the total metal elements excluding lithium in the lithium composite oxide, and mixed with the lithium composite oxide.
[0140] Through the heat treatment, the residual lithium present on the surface of the lithium composite oxide reacted with Ti and Zr to obtain a final product having a surface coated with an oxide containing Ti and Zr.
[0141] Comparative Example 1 (a) A metal salt aqueous solution was prepared by mixing nickel sulfate and manganese sulfate weighed so that the molar ratio of Ni:Mn was 80:20 in a reactor, and the mixture was stirred at 450 rpm for 1,493 minutes to produce Ni. 0.80 Mn 0.20 (OH) 2 The hydroxide precursor had an average composition of 523.3 μm and a radius of 5.0 μm. The volume of the hydroxide precursor calculated using the radius of the hydroxide precursor was 523.3 μm. 3 It was.
[0142] (b) The hydroxide precursor obtained in step (a) is mixed with LiOH (weighed out so that Li has a molar ratio of 1.02 with respect to the total metal element content based on the final product), and then calcined in a calciner. 2 While maintaining the atmosphere, the temperature was increased to 820° C. at 2° C. per minute, and heat treatment was performed at 820° C. for 8 hours to obtain a lithium composite oxide having a radius of 5.0 μm.
[0143] Comparative Example 2 ~ Comparative Example 8 The positive electrode active materials according to Comparative Examples 2 to 8 were prepared in the same manner as in Example 1, except for the conditions described in Tables 3 and 4 below.
[0144] [Table 3]
[0145] [Table 4]
[0146] Comparative Example 9 The lithium composite oxide obtained in step (b) of Comparative Example 1, TiO 2 and ZrO 2 After mixing, it is baked in a furnace. 2 While maintaining the atmosphere, the temperature was raised to 720°C at a rate of 2°C per minute, and the material was heat-treated at 720°C for 8 hours. 2 and ZrO 2 were weighed out so that the contents of Ti and Zr were each 0.1 mol % based on the total metal elements excluding lithium in the lithium composite oxide, and mixed with the lithium composite oxide.
[0147] Through the heat treatment, the residual lithium present on the surface of the lithium composite oxide reacted with Ti and Zr to obtain a final product having a surface coated with an oxide containing Ti and Zr.
[0148] The Ni / Mn molar ratio of the internal bulk (A), the Ni / Mn molar ratio of the external bulk (B), the ratio of the Ni content (mol%) of the external bulk to the Ni content (mol%) of the internal bulk (C), the ratio of the Mn content (mol%) of the external bulk to the Mn content (mol%) of the internal bulk (D), the ratio of the thickness of the external bulk to the radius of the lithium composite oxide (E), and the volume fraction of the external bulk in the total volume of the lithium composite oxide (F) calculated from Tables 1 to 4 are as shown in Table 5 below.
[0149] [Table 5]
[0150] Manufacturing Example 2. Manufacturing of lithium secondary batteries A positive electrode slurry was prepared by dispersing 92 wt% of each positive electrode active material prepared in Preparation Example 1, 4 wt% of artificial graphite, and 4 wt% of PVDF binder in 30 g of N-methyl-2-pyrrolidone (NMP). The positive electrode slurry was uniformly applied to a thin aluminum film having a thickness of 15 μm and dried in a vacuum at 135° C. to prepare a positive electrode for a lithium secondary battery.
[0151] Lithium foil was used as the counter electrode for the positive electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) was used as the separator, and LiPF was dissolved in a solvent of ethylene carbonate and ethyl methyl carbonate in a volume ratio of 3:7. 6 A half-cell was fabricated using an electrolyte in which Zn was present at a concentration of 1.15M.
[0152] Experimental Example 1. Thermogravimetric analysis of positive electrode active material The lithium secondary battery (half cell) manufactured according to Manufacturing Example 2 was charged to 4.3 V at a constant current condition of 0.1 C / 0.1 C at 25° C., and then disassembled to recover the positive electrode active material.
[0153] The recovered positive electrode active material was subjected to a thermogravimetric analysis to evaluate the thermal stability of the positive electrode active material.
[0154] The TGA analysis was performed under the following conditions, and the on-set temperatures at which weight loss began to occur for the positive active materials through the TGA analysis are shown in Table 6 below. Sample: Lithium composite oxide 65mg Measurement atmosphere: Ar gas (gas flow rate: 60 ml / min) Measurement conditions: Heating from 30°C to 350°C at a rate of 10°C / min
[0155] [Table 6]
[0156] Referring to Table 6, it can be seen that the positive electrode active materials according to Examples 1 to 9 have improved thermal stability compared to the positive electrode active materials according to Comparative Examples 1 to 9. In particular, it can be seen that the positive electrode active materials according to Comparative Examples 1 and 9 have lower thermal stability compared to the positive electrode active materials according to the other Comparative Examples. When a positive electrode active material with low thermal stability is used, the positive electrode active material may deteriorate early during charging and discharging of the lithium secondary battery, thereby shortening the life of the lithium secondary battery.
[0157] Experimental Example 2: Evaluation of the electrochemical properties of lithium secondary batteries Each of the lithium secondary batteries (half cells) manufactured in Manufacturing Example 2 was charged to 4.3 V at a constant current condition of 0.1 C / 0.1 C at 25° C., and then discharged to 3.0 V to measure the initial charge capacity, the initial discharge capacity, and the rate capability (rate capability (C-rate)).
[0158] Next, the same lithium secondary battery was charged and discharged 50 times at 45° C. and 1C / 1C within the operating voltage range of 3.0 V to 4.3 V, and the ratio of the discharge capacity at the 50th cycle to the initial capacity (cycle capacity retention) was measured. The measurement results are shown in Table 7 below.
[0159] [Table 7]
[0160] Referring to Table 7, it can be seen that the lithium secondary batteries using the positive electrode active materials according to Examples 1 to 9 in the operating voltage range of 3.0 V to 4.3 V generally have improved initial charge capacity, initial discharge capacity, rate characteristics, and cycle capacity retention rate compared to the lithium secondary batteries using the positive electrode active materials according to Comparative Examples 1 to 9.
[0161] In addition, when comparing the results of the lithium secondary batteries using the positive electrode active materials of Example 1 and Example 9, it can be seen that the rate characteristics are improved as a conductive coating layer is formed on the surface of the lithium composite oxide.
[0162] In addition, in order to evaluate the electrochemical characteristics of the lithium secondary battery in a range of operating voltages in which a relatively high upper limit voltage was applied, the initial charge capacity, initial discharge capacity, rate characteristics, and cycle capacity retention were measured in the same manner as described above, except that the operating voltage range was 3.0 V to 4.5 V.
[0163] The measurement results are shown in Table 8 below.
[0164] [Table 8]
[0165] Referring to Table 8, it can be seen that even in the operating voltage range where a relatively high upper limit voltage (4.5 V) is applied, the lithium secondary batteries using the positive electrode active materials according to Examples 1 to 9 generally have improved initial charge capacity, initial discharge capacity, rate characteristics, and cycle capacity retention, as compared to the lithium secondary batteries using the positive electrode active materials according to Comparative Examples 1 to 9.
[0166] In addition, when comparing the results of the lithium secondary batteries using the positive electrode active materials of Example 1 and Example 9, it can be seen that the rate characteristics are improved by forming a conductive coating layer on the surface of the lithium composite oxide.
Claims
1. A positive electrode active material comprising a lithium composite oxide containing at least nickel and manganese, The lithium composite oxide is divided into an internal bulk and an external bulk that surrounds a surface of the internal bulk and has a Ni / Mn molar ratio of 1.0 or more and less than 2.33; the Ni / Mn molar ratio of the outer bulk is smaller than the Ni / Mn molar ratio of the inner bulk; A positive electrode active material, wherein a volume fraction of the external bulk in a total volume of the lithium composite oxide is 7.4% or more and less than 27.1%.
2. The positive electrode active material according to claim 1 , wherein the Ni / Mn molar ratio of the external bulk is 1.0 to 1.
5.
3. 2. The positive electrode active material of claim 1, wherein the Ni / Mn molar ratio of the inner bulk is greater than 4.26 and less than 9.
00.
4. The positive electrode active material of claim 1 , wherein a molar ratio of Ni to all metal elements excluding lithium in the internal bulk is 0.7 or more and less than 1.
0.
5. The positive electrode active material of claim 1 , wherein a molar ratio of Ni to all metal elements excluding lithium in the external bulk is 0.5 to less than 0.
8.
6. The positive electrode active material according to claim 1 , wherein a ratio of a thickness of the outer bulk to a radius of the lithium composite oxide is greater than 0.025 and less than 0.
10.
7. 2 . The positive electrode active material of claim 1 , wherein a ratio of the Ni content (mol %) of the outer bulk to the Ni content (mol %) of the inner bulk is greater than 0.556 and less than 0.
740.
8. 2 . The positive electrode active material according to claim 1 , wherein a ratio of the Mn content (mol %) of the outer bulk to the Mn content (mol %) of the inner bulk is 2.2 or more and less than 5.
0.
9. The positive electrode active material according to claim 1 , wherein a cationic mixed layer is present on at least a portion of the surface of the external bulk.
10. The cathode active material of claim 1 , wherein the cation mixing ratio of the outer bulk is greater than the cation mixing ratio of the inner bulk.
11. The positive electrode active material according to claim 1, wherein the lithium composite oxide is a cobalt-free lithium composite oxide.
12. The positive electrode active material according to claim 1 , wherein the lithium composite oxide is represented by the following chemical formula 1: [Chemical formula 1] Li a ii 1-(b+c+d) 7N b 71 c 72 d 9 2-e 8 e (where: M1 and M2 are each independently at least one selected from Ti, Zr, Nb, Al, B, V, W, Ca, K, S, P, Sr, Ba, Mn, Ce, Hf, Ta, Cr, Mg, Fe, Zn, Si, Y, Ga, Sn, Mo, Ge, Nd, Gd, and Cu; M1 and M2 do not overlap with each other, X is a halogen element present in a state of substituting oxygen present in the lithium composite oxide, 0.95≦a≦1.05, 0<b≦0.5, 0≦c≦0.05, 0≦d≦0.05, 0≦e≦0.10)
13. The positive electrode active material according to claim 1 , wherein a coating layer containing a metal oxide represented by the following Chemical Formula 2 is formed on at least a portion of a surface of the lithium composite oxide: [Chemical 2] Li f M3 g O h (where: M3 is at least one selected from Ni, Mn, Co, Ti, Zr, Nb, Al, B, V, W, Ca, K, S, P, Sr, Ba, Mn, Ce, Hf, Ta, Cr, Mg, Fe, Zn, Si, Y, Ga, Sn, Mo, Ge, Nd, Gd, and Cu; 0≦f≦10, 0≦g≦8, 2≦h≦13, except when f and g are both 0.
14. The positive electrode active material according to claim 13 , wherein M3 includes at least one selected from Ti and Zr.
15. A positive electrode comprising the positive electrode active material according to any one of claims 1 to 14.
16. A lithium secondary battery using the positive electrode according to claim 15.
Citation Information
Patent Citations
Non-aqueous electrolyte secondary battery
JP2010050079A
Compound oxide, complex transition metal compound, production method of compound oxide, cathode active material for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
JP2014040363A
Metal composite hydroxide and method for producing same, positive electrode active substance for non-aqueous electrolyte secondary battery and method for producing same, and non-aqueous electrolyte secondary battery
WO2019163845A1
Cobalt-free layered positive electrode material and preparation method therefor, positive electrode plate, and lithium ion battery
WO2021143374A1
Composite cobalt-free positive electrode material and preparation method therefor
WO2021238202A1